Elevated Temperature and Exposure to Copper Leads to Changes in the Antioxidant Defense System of the Reef-Building Coral Mussismilia harttii - da Silva Fonseca, Juliana; de Barros Marangoni, Laura Fernandes; Marques, Joseane Aparecida; Bianchini, Adalto (Frontiers in Physiology, 2021)
The frequency and severity of coral bleaching events have increased in recent years. Global warming and contamination are primarily responsible for triggering these responses in corals. Thus, the objective of this study was to evaluate the isolated and combined effects of elevated temperature and exposure to copper (Cu) on responses of the antioxidant defense system (ADS) of coral M. harttii. In a marine mesocosm, fragments of the coral were exposed to three temperatures (25.0, 26.6 and 27.3 ⁰C) and three concentrations of Cu (2.9, 5.4 and 8.6 µg/L) for up to 12 days. Levels of reduced glutathione (GSH) and the activity of enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST) and glutamate cysteine ligase (GCL) were evaluated on the corals and symbionts. The short exposure to isolated and combined stressors caused a reduction in GSH levels and inhibition of the activity of antioxidant enzymes. After prolonged exposure, the combination of stressors continued to reduce GSH levels and SOD, CAT and GCL activity in symbionts and GST activity in host corals. GCL activity was the parameter most affected by stressors, remaining inhibited after 12-days exposure. Interesting that long-term exposure to stressors stimulated antioxidant defense proteins in M. harttii, demonstrating a counteracting response that may beneficiate the oxidative state. These results, combined with other studies already published suggest that the antioxidant system should be further studied in order to understand the mechanisms of tolerance of South Atlantic reefs.